Why has Myanmar not achieved democratization? A comparative case study of Myanmar and South Korea - Lim, Samantha Si En (Nanyang Technological University, 2023)
Since 1962, Myanmar has been governed under the military, the Tatmadaw, until the 2015 elections when the National League for Democracy party won. However, Myanmar struggled to sustain democracy and eventually returned to military rule following the 2021 military coup. Current literature emphasizes the need for Myanmar to democratize for development. In this paper, I aim to answer the question: Why has Myanmar not achieved democratization? I will be comparing Myanmar’s political situation to South Korea’s trajectory of development under authoritarian leader Park Chung-hee, to identify key differences in the growth of both countries. Through comparison with the South Korean model, I posit that Myanmar has not achieved democratization due to the lack of political legitimacy of the government. Political legitimacy is attained through equitable redistribution of resources and social coherence. With greater political legitimacy, social capital which can build state-public trust would be strengthened, bringing about social and economic development. The absence of political legitimacy and concomitantly, development, inhibits Myanmar’s ability to democratize. This paper will also consider the domestic issues in Myanmar and its unique political struggles. The comparative analysis will add to the literature of democratization and give further insight into the possibilities of Myanmar politics and governance.